Penentuan Umur Simpan Sirup Pala Menggunakan Metode ASLT (Accelerated Shelf Life Testing) Dengan Pendekatan Arrhenius - Fallen B. Sandana; Dekie Rawung; Maya Ludong; Christine Mamuaja (Universitas Sam Ratulangi, 2014)
ABSTRACTNutmeg syrup is one way to diversify products of nutmeg. IKM â€œSari Fruitâ€ is one of nutmeg syrup producers in North Sulawesi, especially in the District Sitaro. However, nutmeg syrup in the market has not specified expiration date. One method that can be used to determining the shelf life of food product is ASLT (Accelerated Shelf Life Testing). This research aims to determine the shelf life of nutmeg syrup production IKM